Exploring the use of physical rehabilitation for sepsis survivors: a scoping review - Michelle E Kho; Bram Rochwerg; Jenna Smith-Turchyn; Christopher Farley; Jordon L Hvizd; Anastasia N L Newman; Heather O’Grady; Sophia Werdens Abram; Neeraja Nannapaneni; Shannon McKenney (BMJ Open, 2025)
Objectives To explore the use, parameters, safety and outcomes of physical rehabilitation for adults with sepsis.Design We conducted a scoping review following the Joanna Briggs Institute framework.Participants Studies were eligible for inclusion in the study if they included: (1) adults 18 and older, (2) with a previous diagnosis of sepsis, (3) using a physical rehabilitation intervention at any point of sepsis management, (4) published in English or French.Procedure We searched seven databases and screened titles and abstracts, reviewed full texts and performed data extraction independently and in duplicate. We summarised findings narratively using the “population, context, concept” framework and used descriptive statistics where appropriate. End-users reviewed and commented on study findings.Results We included 58 studies, representing 77 434 participants, with the majority (79%) being published in the last decade. A large proportion (36%) of physical rehabilitation interventions included exercise and were overseen by a physical therapist (41%). The parameters of the interventions varied widely. However, all interventions (100%) were hospital based and the interventions implemented appeared safe. Of the 28 studies evaluating effectiveness of the intervention, function improved in most studies (78%) following physical rehabilitation.Conclusion Research addressing physical rehabilitation for patients with sepsis is increasing. Physical rehabilitation appears safe and may improve functional outcomes in those with sepsis. Future research should report details of intervention parameters and evaluate rehabilitation post-hospital discharge to maximise impact on function and quality of life for sepsis survivors.Registration The protocol was registered on Open Science Framework Registries (Registration DOI: https://doi.org/10.17605/OSF.IO/2EPJ6).